2012
DOI: 10.1155/2012/923818
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Pin Surface Roughness for Friction Forces of Ultrathin Perfluoropolyether Lubricant Film on Magnetic Disks by Pin-on-Disk Test

Abstract: We fabricated supersmooth probes for use in pin-on-disk sliding tests by applying gas cluster ion beam irradiation to glass convex lenses. In the fabrication process, various changes were made to the irradiation conditions; these included one-step irradiation of Ar clusters or two-step irradiation of Ar and N2clusters, with or without Ar cluster-assisted tough carbon deposition prior to N2irradiation, and the application of various ion doses onto the surface. We successfully obtained probes with a centerline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The wear resistance of the UHMWPE against a metal femoral head deposited with DLC by MPCVD showed better performance [6]. The surface of DLC can be modified on the nanometer scale using high energy ion irradiation [7] and self bias [8]. Ion irradiation has been used to produce a wide variety of modifications in different materials due to the energy loss of the ions as they travel through the material.…”
Section: Imentioning
confidence: 99%
See 1 more Smart Citation
“…The wear resistance of the UHMWPE against a metal femoral head deposited with DLC by MPCVD showed better performance [6]. The surface of DLC can be modified on the nanometer scale using high energy ion irradiation [7] and self bias [8]. Ion irradiation has been used to produce a wide variety of modifications in different materials due to the energy loss of the ions as they travel through the material.…”
Section: Imentioning
confidence: 99%
“…Modifications in DLC thin films by ion irradiation has been previously studied for changes in the properties [9,10]. Recently H. Tani et al [7] have reported that two step Ar-N2 GCIB irradiation has resulted in the reduction of surface roughness in DLC films. In this context it will be interesting to study the influence high energy ion irradiation on surface roughness of DLC films synthesized by microwave plasma CVD.…”
Section: Imentioning
confidence: 99%